Human Capital Development Role of HR during Mergers and Acqusitions - Rizvi, Yasmeen (The South East Asian Journal of Management, 2010)
The need for corporate firms to gain competitive advantage in a highly competitive global environment has necessitated the adoption of innovative strategies, one of them being mergers and acquisitions. Selden and Colvin (2003) have stated that 70%-80% of acquisitions fail, meaning that they create no wealth for the share owners of the acquiring company. Schmidt (2003) has identified five major roadblocks to M & A success, three of which are HR issues. It has been established that there is a strong direct correlation between human resource involvement and 'success' in mergers and acquisitions (Schmidt, A.J., 2003). A positive association was found between human capital indicators and organizational performances (Seleim, Ashour, and Bontis, 2007). It was found that human capital development and enhancement in organizations contribute significantly to organizational competencies which in turn became a great boost for further enhancing innovativeness (Bontis and Fitzenz, 2002). As a research gap has been found in the study of human capital development interventions used during mergers and acquisitions, the present research aims to study the role of human capital development interventons used during integrations stage of mergers and acquisitions. Both quantitative as well as qualitative study has been carried out to capture a more complete portrayal of the subject.